Should We Tax Sugar and If So How?. (8th October 2018) - Lloyd, Peter; MacLaren, Donald
Abstract: This article reviews empirical studies of proposals to tax sugary products in Australia. A corrective tax must be designed carefully if it is to increase national welfare. There is an underlying problem in designing such a tax because consumers are heterogeneous. The best choice of goods to be taxed is the group of sugar‐sweetened‐beverages, the best tax base is the sugar content and the best tax form is a progressive specific tax with two or more levels. We recommend initial rates that are equal to those of the UK tax on SSBs.